2000
DOI: 10.1037/0033-2909.126.6.925
|View full text |Cite
|
Sign up to set email alerts
|

Beyond behaviorism: On the automaticity of higher mental processes.

Abstract: The first 100 years of experimental psychology were dominated by 2 major schools of thought: behaviorism and cognitive science. Here the authors consider the common philosophical commitment to determinism by both schools, and how the radical behaviorists' thesis of the determined nature of higher mental processes is being pursued today in social cognition research on automaticity. In harmony with "dual process" models in contemporary cognitive science, which equate determined processes with those that are auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
513
0
14

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 917 publications
(554 citation statements)
references
References 139 publications
(181 reference statements)
14
513
0
14
Order By: Relevance
“…I conjecture that the disagreement stems in part from the fact that mental actions are typically automatic and that there are differing intuitions about the import of automaticity with respect to agency. Work in social psychology has cataloged the pervasiveness of automaticity even in goal directed behavior where control is conceived as delegated to the environment, obviating any need for conscious control on the part of the subject (Bargh and Ferguson (2000)). Bernhard Hommel (2000) has spoken of intention as a "prepared reflex", the upshot being that intentions allow the environment to take control of behavior without the need of further intervention (control) by the subject.…”
Section: Mental Ballisticsmentioning
confidence: 99%
“…I conjecture that the disagreement stems in part from the fact that mental actions are typically automatic and that there are differing intuitions about the import of automaticity with respect to agency. Work in social psychology has cataloged the pervasiveness of automaticity even in goal directed behavior where control is conceived as delegated to the environment, obviating any need for conscious control on the part of the subject (Bargh and Ferguson (2000)). Bernhard Hommel (2000) has spoken of intention as a "prepared reflex", the upshot being that intentions allow the environment to take control of behavior without the need of further intervention (control) by the subject.…”
Section: Mental Ballisticsmentioning
confidence: 99%
“…Goals guide attention and behavior (e.g., Bargh & Ferguson, 2000) and represent a standard for evaluating performance (e.g., Bandura, 1989), which in turn affects subjective well-being (e.g., Brunstein, 1993). Given the importance of goals for adaptation and development, it is not surprising that there are numerous theories that attempt to explain and understand the processes of goal setting (e.g., Austin & Bobko, 1985;Locke & Latham, 1990), goal striving (e.g., Freund & Baltes, 2002; Gollwitzer & Brandstätter, 1997) and goal adjustment (e.g., Brandtstädter & Rothermund, 2002;Wrosch, Scheier, Carver, & Schulz, 2003).…”
Section: Goal Conflict and Goal Facilitationmentioning
confidence: 99%
“…Ewing and Cervero (2010) identified urban design qualities that influence walkability-that is, the "5Ds," density, diversity, design, distance to transit and distance to opportunities. Corroborating these findings, public health research shows how such physical and environmental factors can influence behavioral patterns related to health, especially with regards to mode choice and active transportation (Salmon et al 2003, Bargh and Ferguson 2000, Bargh and Chartrand, 1999, Sallis et al 1999. Examining how environmental attributes influence physical activity in general, Sallis and Owen (2002) showed that factors such as aesthetics, convenience and access resulted in higher active travel levels.…”
Section: Literature Reviewmentioning
confidence: 99%